A Detailed Analysis of Sediment Particle Sizes and Clogging in Permeable Pavements. Issue 4 (27th February 2017) - Nichols, Peter W. B.; Lucke, Terry
Abstract : The trapping of sediments within permeable interlocking concrete pavements (PICPs) during infiltration is a key process that contributes to their pollution removal performance. This process also leads to clogging which decreases infiltration capacity and reduces pollution removal performance. Previous studies have shown clogging to be caused by a number of factors, including the trapping of fine particles, construction techniques, the lack of maintenance, and the mass of the trapped sediments. However, results of these studies have been varied, and the processes governing clogging are not well understood. This field study, undertaken over 12 months, measured the infiltration rates of PICPs that had been in service for a number of years. The study examined sediment extracted from the surface joints of pavements in order to correlate reduced infiltration with sediment particle size distributions (PSDs). Principal component analysis (PCA) was used to compare the differences in infiltration rates and the differences in PSD size class groups between the sites and sub‐sites. This study found it was the 251–550 μm particle sizes that explained the most variation at sites with lower measured infiltration rates. A better understanding of sediment PSDs and PICP clogging should help designers to install these systems with more confidence in their long‐term infiltration and pollution reduction performance. Abstract : The focus of this study is to identify factors which are most likely to influence clogging in permeable interlocking concrete pavements, with a focus on sediment particle sizes. The study finds that sites with similar sediment particle size distribution can have different surface infiltration rates and the 251–550 µm particle sizes that explain the most variation at sites with lower measured infiltration rates are identified.